Organization of the educational process in the university during the pandemic - Petrovna Gadzaova, Lyudmila (2021)
In modern conditions of the pandemic and related economic and social changes, the quality of knowledge acquired by students both online and in the classroom has become even more important in the field of higher education and university pedagogical practice. The student's attitude towards their future professional and research activity and their understanding of the purpose, necessity, usefulness, and benefits of acquired professions are also important. This proves the increasing organizational complexity of the educational process and creation of effective psychological and pedagogical conditions in the educational environment of universities, on which the professional competence of future specialists largely depends. The article is devoted to the study of the relationship and interdependence of students’ educational, scientific, and cultural orientations in the course of higher education. It analyses the attitude of students towards the educational process and the formation of professional identity as the main value orientation for a given period of study. Modern media communication technologies are actively used in the educational process. A consistent and systematic approach is provided with the help of the Periscope application, which is a platform for distance learning. It allows holding open classes and workshops, participating and watching the learning process in real-time, broadcasting interesting events (conferences, exhibitions, seminars). Special attention is paid to media activity in social networks. Vkontakte, Instagram, and Facebook are the applications developed and used as effective platforms for sharing the news, announcements, polls, discussions, photo and video reports about university events. For instance, last year the North Ossetian State University became one of the leaders of the rating based on the results of monitoring the information openness of universities. The rating was presented by the Ministry of Education and Science of the Russian Federation during the conference devoted to information interaction. The qualification acquired within the university study gives graduates the opportunity, on the one hand, to actively participate in the design, implementation, and further development of complex applied systems. On the other hand, it provides a basis for the scientific solution of related problems within applied research. In addition, an essential element of the master's degree is the creation of a professional area, which opens up the opportunity for students to acquire the appropriate additional qualifications necessary for leadership and managerial positions in addition to the content of education and professional practice.